The role of community pharmacists with Syrian migration background in addressing healthcare needs of migrant population in Germany: a qualitative study - Saleh Aljadeeah; Aleksandra Borek (BMC Health Services Research)
Abstract Background Migrants often face various barriers to their access to healthcare services. Community pharmacists play a crucial role in offering accessible, patient-centred healthcare services. However, little is known about the unique role of migrant pharmacists in addressing the healthcare needs of migrants. Therefore, this research aimed to investigate the role of migrant pharmacists in providing access to healthcare for migrant populations in Germany. Methods This exploratory qualitative study used semi-structured interviews with Syrian migrant pharmacists working in Germany. Participants were recruited through contacts from the author’s professional network. All interviews were remotely conducted, recorded, transcribed verbatim, and analyzed using inductive thematic analysis to ensure that findings are grounded in the original data. Results Ten Syrian migrant pharmacists were interviewed. The findings highlighted the multifaceted role of migrant pharmacists, extending beyond medicine dispensing to bridging gaps in healthcare access through culturally appropriate services. Their ability to communicate in patients’ native languages and provide tailored advice positioned them as key facilitators in addressing migrants’ healthcare challenges. Participants described their proactive involvement in health promotion, particularly in raising awareness about preventive measures such as vaccinations. However, they also faced significant challenges, including regulatory constraints and resource limitations, which they navigated through various adaptive strategies. Conclusions This study explored the role of migrant pharmacists, particularly those from Syria, in addressing the healthcare needs of migrants in Germany. Their ability to communicate in both Arabic and German and to understand cultural nuances is a key asset that helps overcome language barriers, making them an invaluable resource for migrant patients. The research highlighted the multifaceted nature of the pharmacists’ roles, which extend beyond dispensing medicines, bridging gaps in healthcare access through culturally sensitive and linguistically appropriate services. The study also shed light on the adaptive strategies and recommendations for strengthening the role of migrant pharmacists.